Consolidators and survivors: formal self help and self-help homebuilders in South Africa - Hart, Timothy (My University, 1984)
It is widely acknowledged that self-help procedures produce housing (Harms, 1982), but there are differing perspectives on the contexts and motives leading to the emergence of the self-help housing phenomenon; and the significance of self-help housing action in the lives of the actors themselves (Martin, 1984). The first issue has been the focus of sustained debate elsewhere (Burgess, 1978; 1982; Harms, 1976; 1982; Lea, 1979; Turner, 1978; 1982), but the second has remained largely the domain of the supporters of self-help housing strategies. This discussion is a first attempt at focusing critical scrutiny on the impact of self-help housing among those who are most intimately involved in it, the self-help homebuilders. This is not a clear-cut task, because the existing self-help literature provides few leads. The bulk of critical work focusing on self-help is a response to the glowing descriptions of self-help enterprise that emerged from the pens of fieldworkers in the squatter settlements of Latin America (Burgess, 1978). Most of this criticism places the self-help squatter phenomenon within a class-based framework of domination and subjection. Here, the group is the unit of analysis, and self-help action is seen to be the collective response to structural poverty. We find this analysis useful, but somewhat unsatisfactory in the context of our own research. Firstly, having worked among self-help homebuilders, it is apparent, to us that self help means different thing to different people. Whatever the overarching principle behind the emergence of self help, it is clear that every self-help scheme incorporates winners and losers, opportunists and unwilling co-optees, developers and survivors (Martin, 1984). Secondly, self-help housing and squatting are by no means synonymous in South Africa. Around South African cities, controlled, state-sanctioned self-help has emerged in the wake of ailing mass housing schemes. Self-helpers in this situation are not squatters, but may be relocatees, refugees from chronic overcrowding elsewhere, or even speculators keen to grab new residential possibilities. All enter the self-help arena with different chances of making out, some determined by entry, and others by contextual and personal factors beyond this.
African Studies Seminar series. Paper presented October, 1984